2021
DOI: 10.1111/ajt.16440
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis and meta-regression of outcomes for adult living donor liver transplantation versus deceased donor liver transplantation

Abstract: Prior single center or registry studies have shown that living donor liver transplantation (LDLT) decreases waitlist mortality and offers superior patient survival over deceased donor liver transplantation (DDLT). The aim of this study was to compare outcomes for adult LDLT and DDLT via systematic review. A meta‐analysis was conducted to examine patient survival and graft survival, MELD, waiting time, technical complications, and postoperative infections. Out of 8600 abstracts, 19 international studies compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 75 publications
2
57
0
Order By: Relevance
“…Our findings are comparable to those reported in a previously published systematic review of LDLT versus DDLT for adult patients with chronic liver failure, where both patient and graft survival were superior in the LDLT group. ( 4 ) This is not an unexpected finding; although LDLT tends to be more technically challenging, it provides timely access to a high‐quality organ (with minimal preservation time) from extremely healthy donors. According to our analysis, patients undergoing LT for an indication of ALF do not appear to have as pronounced improved survival with LDLT as patients with chronic as well as combined acute and chronic liver disease.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Our findings are comparable to those reported in a previously published systematic review of LDLT versus DDLT for adult patients with chronic liver failure, where both patient and graft survival were superior in the LDLT group. ( 4 ) This is not an unexpected finding; although LDLT tends to be more technically challenging, it provides timely access to a high‐quality organ (with minimal preservation time) from extremely healthy donors. According to our analysis, patients undergoing LT for an indication of ALF do not appear to have as pronounced improved survival with LDLT as patients with chronic as well as combined acute and chronic liver disease.…”
Section: Discussionmentioning
confidence: 91%
“…( 2 ) Living donor liver transplantation (LDLT) can decrease waiting times and offer better quality graft organs at the expense of higher biliary and vascular complications. ( 3 ) A recently published systematic review and meta‐regression of outcomes among adult recipients of LDLT and DDLT by Barbetta et al ( 4 ) reported lower LDLT mortality at 1, 3, and 5 years with similar graft survival. However, data on long‐term outcomes from pediatric populations are lacking, and a systematic review of pediatric LDLT versus DDLT outcomes in the pediatric population has not been carried out to date.…”
mentioning
confidence: 99%
“…With increasing experience over the past two decades, many of the early technical challenges observed in living donor liver transplantation (LDLT) have been resolved, including inflow modulation for potentially small-for-size grafts. Recent data have demonstrated that LDLT can provide superior graft and patient survival when compared to deceased donor liver transplant (DDLT), for both pediatric and adult recipients [2][3][4][5][6]. However, even in experienced centers, 40% of living liver donors experience postoperative complications, and thus donor safety and informed consent remain central to the LDLT procedure [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…6 Several studies have shown improved post-transplant survival with living donor compared to waiting for a deceased donor. [7][8][9][10][11][12] Moreover, studies examining outcomes of living liver donors in the United States have shown excellent results with low rates of Clavien-Dindo grade III or higher complications, excellent long-term quality of life, and very low mortality that is comparable with living kidney donors. 10,[13][14][15] Due to the rising utilization of living liver donation in the West, we wholeheartedly agree that ongoing efforts to monitor and optimize long-term donor outcomes are paramount.…”
Section: Introductionmentioning
confidence: 99%